Business Value from Closed-loop Supply Chains - Otto Koppius; Ã–znur Ã–zdemir AkyÄ±ldÄ±rÄ±m; Erwin van der Laan (International Journal of Supply Chain Management, 2014)
This study provides a complete framework to define and classify the value that firms can attain by their closed-loop supply chains (CLSC) and analyzes the role of information systems (IS) in this process. We present a novel typology to identify the four value types a firm can generate in CLSCs, namely sourcing, environmental, customer, and informational value. Particularly the last two types have not been recognized in literature. We adopt a case methodology and analyze 8 cases to illustrate the generation of each value type through CLSCs and highlight the role that IS play in this value generation. We ground our analysis on the integrative model of IT business value in [30] which considers the role of external business partners, which is essential to CLSCs. We find 3 key results: (1) IS is an essential enabler for all value types, (2) while sourcing value and to some extent environmental value, can be created with IS internal to the firm, the novel value types (customer and informational) can only be created with extraorganizational IS, (3) the value created by extraorganizational systems can only be created if the appropriate intraorganizational systems are in place. Our findings show that substantial value can be gained from implementing IS in CLSCs but stakeholder collaboration is necessary to reap the full value. This is an important managerial insight for the firms who still consider CLSC activities as costly and do not notice all the benefits that they can obtain from CLSCs.